Evaluation of Some Hematological Parameters in HCV Infected Patients Among Blood Donors at Thi-Qar Province: Evaluasi Beberapa Parameter Hematologi pada Pasien yang Terinfeksi HCV di Antara Donor Darah di Provinsi Thi-Qar - Al-Jabery, Ahmed Hieran Ramadhan; Okab, Hayder Fadhil; Alkafaji, Ali Obeid Ibrahim; Hammoud, Ali Hussein; Saad, Saif Al-Din; Radhi, Radha Mohammed; Naji, Abbas Mohammed; Al-Abadi, Zain Al-Abidin Adel; Aneed, Mohammed Hassan (Academia Open, 2024)
Hepatitis C virus is a major health problem because of its effect on the liver and health and its being life-threatening if not treated early. It also affects the blood parameters of those infected. The current study conducted in Thi-Qar province revealed changes in some blood parameters of the infected group compared to the control group, where a slight decrease was recorded in WBCs, RBCs, PCV, MCV, MCH, PLT, Lymp. but no significant differences were found, except for red blood cells, which were 0.03 at a significant level 0.05. It was also found that the highest infection rate was in the age group of 30-39 years, while no infection was recorded in the age group of 50-59 years. Highlights: <div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="1d32c6a8-77a1-4611-ba5d-da794fea2b81" data-message-model-slug="gpt-4o"> Hepatitis C impacts liver health and alters blood parameters. Significant RBC change noted; highest infection in 30–39 age group. No infections in the 50–59 age group recorded. Keywords: HCV, Hematological, ELISA, Thi-Qar